Peran Tenaga Administrasi Dalam Meningkatkan Pelayanan Akademik Sekolah - Fatimah Azzahra (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This research journal is a literature study that discusses the role of administrative staff in improving school academic services. This study analyzes the responsibilities of administrative staff, the problems faced, and efforts to improve professionalism to support the smooth academic process in schools. This study shows that administrative staff play an important role in effective academic administration management, which has a direct impact on the quality of services provided to students, teachers, and parents. The results of the study indicate that improving skills, using information technology, and appreciating the role of administrative staff are very important to achieve optimal academic services. Therefore, administrative staff play an important role in building an excellent education system.